A new species of gall wasp Diastrophus Hartig, 1840 (Hymenoptera: Cynipidae) from Sichuan, China - Fang, Zhiqiang; Hu, Wenqian; Nieves-Aldrey, José Luis; Mccormack, Koorosh; Tang, Chang-Ti; Zhu, Ying; Csóka, György; Hearn, Jack; Sinclair, Frazer H.; Mao, Kangshan; Stone, Graham N.; Zhang, Y. Miles (Zootaxa, 2025)
We describe a new species of gall wasp associated with Rubus lambertianus Ser. in Sichuan, China: Diastrophus emeiensis Hu, Nieves-Aldrey, Zhang & Fang sp. nov. (Cynipidae: Diastrophini) based on morphological and molecular data. This is the first Diastrophus Hartig, 1840 species recorded from mainland China, and is recovered as the sister group to the rest of Diastrophus based on our phylogenetic analysis. The diagnosis, distribution, and biology of D. emeiensis is provided, along with a brief discussion of the evolutionary history of Diastrophus.